NILAI-NILAI HEROISME TOKOH UTAMA DALAM ROMAN LARASATI KARYA PRAMOEDYA ANANTA TOER - Laila, Laila; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe background of this research was the writerâ€™s interest to explore the heroic values in Roman Larasati by Pramoedya Ananta Toer. Theories used in this research were the definition of romance, intrinsic and extrinsic elements in romance, heroic values, and literature learning. Method used in this research is descriptive in qualitative form. Results analysis found were the elements of self-sacrfice, beliefs of Pancasila and UUD 1945, national conscience as heroic value, and the implementation in learning. The implementation of this research was particularly in the literature learning in high school grade XII semester 2 at basic competence 3.9 and 4.9. Hopefully the results of this research were beneficial as reference for teachers in teaching literature at school. From this research, messages and heroic values could be taken.Keywords: Heroic Values, Romance, Implementation